Situation Report: Romania, 21 July 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Brandt to Romania Dragan Again Criticizes WFTU Romanian Press Reports on Budapest Summit Experiments Going on in the Economy Private Restaurants and Pensions Set Going Cooperation with Foreign Countries Krag to Romania Klaus Visit Ends